MENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI BERMAIN PERMAINAN TRADISIONAL LOMPAT TALI PADA KELOMPOK B TK AISYIYAH BUSTANUL ATHFAL DESA AURSATI KECAMATAN TAMBANG KABUPATEN KAMPAR - Zahari, Afrizal; Zainur, Zainur; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of observations in the field it was found that the ability of children in jumping is still low, besides that the motivation of the children themselves is also very lacking. The gross motor learning process is usually always done outside the classroom, usually after the child is bored the child instead plays alone running around and is not organized or talking to friends so as to make the learning situation not conducive anymore. This can be seen when learning about jumping rope games, many children are not able to do it. The purpose of this study was to determine efforts to improve children's gross motor skills through playing traditional jump rope games in group B Kindergarten Aisyiyah Bustanul Athfal Aursati Village, Tambang District, Kampar Regency. The population in this study were kindergarten students Aisyiyah Bustanul Athfal Aursati Village, Tambang District, Kampar Regency, amounting to 17 people, using total sampling techniques, then the sample in this study amounted to 17 people. Based on the results of the research and discussion stated, it can be seen that the initial condition of the child before and the action shows gross motor skills in children shows that 2 (12%) children are able to jump in balance, 1 (6%) children are able to jump in balance and 3 (18%) children are able to jump out of shape. After taking pre-action, actions were taken in cycle I and cycle II which increased. In the motor skills of balance cycle I 9 (53%) children are able to jump in balance in cycle II increased to 16 (94%) children are able to jump in balance. In the motor ability of strength 9 (53%) children are able to jump strongly, in the second cycle increased to 16 (94%) children are able to jump strongly. In the motor ability of 9 (53%) the ability to jump with lungs in cycle II increased 17 (100%) children were able to jump with l Shape.Key Words: Rough Motor, Jump Rope Game